Environmental Transformations and Cultural Responses : Ontologies, Discourses, and Practices in Oceania - Dürr, Eveline; Pascht, Arno (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book explores the various ways in which different communities and peoples in Oceania respond to and engage with recent environmental challenges and concurrent socio-political reconfigurations. Based on empirical research, the book discusses topics such as belonging, emotional attachment to land, and new forms of environmental knowledge. The theoretical framework of the book is inspired by current debates among diverse conceptualisations of the environment and thus, of various ways of knowing, making sense of, and interacting with worlds. With this focus in mind, the book provides new insights into recent socio-cultural and environmental dynamics in the Pacific.- Resumé vydavatel
Keywords: klimatické změny -- sociální aspekty -- Oceánie (souostroví); environmentální sociologie -- Oceánie (souostroví); příroda -- antropogenní vlivy -- Oceánie (souostroví); climate changes -- social aspects -- Oceania Archipelago; environmental sociology -- Oceania Archipelago; nature -- anthropogenous influences -- Oceania Archipelago; elektronické knihy; sborníky; electronic books; papers of several authors